Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1590/1983-21252018v31n401rc
|View full text |Cite
|
Sign up to set email alerts
|

Green Fertilization With Residues of Leguminous Trees for Cultivating Maize in Degraded Soil

Abstract: The objective of this study was to evaluate the effects of the addition of parts of leguminous trees on the growth and nutrition of maize (Zea mays L.), as well as on the chemical attributes of a degraded soil, 65 days after applying the residues. The experiment was conducted in pots, in a randomized block design with ten treatments and four replicates. The evaluated treatments were: T1 - No residues of leguminous trees, T2 - Leaves of Mimosa caesalpiniifolia, T3 - Branches of Mimosa caesalpiniifolia, T4 - Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
5
0
2
Order By: Relevance
“…The techniques used showed coherent results, as a whole, making it possible to identify which residues of the studied legume species have the greatest potential for use as fertilizer, unlike the result observed by Oliveira et al (2018), who adopted univariate techniques for analyzing data of a similar study and did not find responses that allowed them to indicate the best species or part of the plant for this purpose.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The techniques used showed coherent results, as a whole, making it possible to identify which residues of the studied legume species have the greatest potential for use as fertilizer, unlike the result observed by Oliveira et al (2018), who adopted univariate techniques for analyzing data of a similar study and did not find responses that allowed them to indicate the best species or part of the plant for this purpose.…”
Section: Resultsmentioning
confidence: 89%
“…The residues of Jurema leaves led to higher values of Ca, IN and TOC in soil, leaf contents of K and Ca, and total dry mass (Figure 2). In this case, Jurema leaves, besides having a relatively low C/N ratio (Table 2), also have a larger contact surface (tiny leaflets), which facilitates their decomposition and, consequently, the availability of nutrients (OLIVEIRA et al, 2018). It is also observed that the residues of Jurema leaves influenced higher values of potential acidity and lower values of pH.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…No estado do Pará, conforme o manual de calagem e adubação do estado, faixa de K acima de 90 mg dm 3 são considerados alto para a resposta de diferentes culturas [19]. A alta concentração de K no solo é uma característica do uso da gliricídia [20].…”
Section: Resultsunclassified